ENSURING SUSTAINABLE DEVELOPMENT THROUGH TAX REGULATION IN THE TRANSITION TO A GREEN ECONOMY IN THE COUNTRY. (Universal International Scientific Journal, 2026)
This article provides information on the benefits provided to enterprises producing environmentally friendly products in Uzbekistan during the transition to a green economy and the fiscal policy implemented during the transition to a green economy.
Keywords: green, economy, privilege, tax, ecological, area, efficiency.